Development of power conditioners and controllers for microgrids - Li, Yun Wei (2008)
Microgrid is a cluster of loads and distributed generation (DG) systems operating together within a certain local area. Being a systematic organization of DG systems, the microgrid has larger power capacity and more control flexibilities to fulfill system reliability and power quality requirements, in addition to all the inherited advantages of a single DG. Furthermore, as a system approach to realize the emerging potential of DG system, the microgrid can combat problems caused by the unconventional behaviors of DG. Proper operation of a microgrid requires robust local voltage regulation as well as dispatched power generation. During a power system interruption, the microgrid must disconnect itself from the utility and protect the loads in it. After the utility voltage is restored, the microgrid should synchronize with the utility and reconnect to it smoothly.